If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (h + 7)(h + 3) = 0 Reorder the terms: (7 + h)(h + 3) = 0 Reorder the terms: (7 + h)(3 + h) = 0 Multiply (7 + h) * (3 + h) (7(3 + h) + h(3 + h)) = 0 ((3 * 7 + h * 7) + h(3 + h)) = 0 ((21 + 7h) + h(3 + h)) = 0 (21 + 7h + (3 * h + h * h)) = 0 (21 + 7h + (3h + h2)) = 0 Combine like terms: 7h + 3h = 10h (21 + 10h + h2) = 0 Solving 21 + 10h + h2 = 0 Solving for variable 'h'. Factor a trinomial. (7 + h)(3 + h) = 0Subproblem 1
Set the factor '(7 + h)' equal to zero and attempt to solve: Simplifying 7 + h = 0 Solving 7 + h = 0 Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + h = 0 + -7 Combine like terms: 7 + -7 = 0 0 + h = 0 + -7 h = 0 + -7 Combine like terms: 0 + -7 = -7 h = -7 Simplifying h = -7Subproblem 2
Set the factor '(3 + h)' equal to zero and attempt to solve: Simplifying 3 + h = 0 Solving 3 + h = 0 Move all terms containing h to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + h = 0 + -3 Combine like terms: 3 + -3 = 0 0 + h = 0 + -3 h = 0 + -3 Combine like terms: 0 + -3 = -3 h = -3 Simplifying h = -3Solution
h = {-7, -3}
| 0.12=(x)(0.19)+(1-w)(0.08) | | 2x-3-12/4-5 | | 90+59+x=180 | | a^2+11a= | | n^2+15n= | | 0.81h^3-h-13= | | 2x+1-x-1=1 | | 103-2x=180 | | 3x+15=21x+4 | | 103-2x=18 | | 6x+4=7x-9 | | -x^2+10x= | | -m^2-7m= | | 5x+x^2=126 | | (4x^2)-6x=9 | | -m^2+15m= | | -(4x-3)-(7x-5)+11=-7(x-1)-(7x+6)+3 | | 45=3x+x^2 | | 10x-12=12+4x | | 1.5=0.5*9.81*t^2 | | f(t)=16t^2+32t+90 | | 17-n=10 | | (c+4)(2c+7)= | | 6x-12=9x+15 | | A=11x+kx | | 15x=13x+12 | | 4v=40 | | 10x+24=Xb+ax+ab | | log(6)(6x-1)=1 | | 3(2x+6)=4x-8 | | z=2z+3z | | 252=45t |